The study of eclampsia as a cause of severe acute maternal morbidity - Lakshmi S. K., Yoga; R., Suvarna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: “SAMM” refers to the morbidity a woman actually suffers1. The identification of Eclampsia as a cause of severe maternal morbidity has emerged as a promising complement or alternative to the investigation of maternal deaths. The most common tool used to identify SAMM is by WHO criteria. Incorporation of near-misses into maternal death enquiries would improve the quality of care and its standardization. Methods: A descriptive study of SAMM in the department of OBG in KIMS hospital done between Jan 2013 to June 2014. The total number of deliveries during this period were 2786. There were 43 cases of Eclampsia as a cause of SAMM. Among this, 1 case was admitted in ICU due to peripartum cardiomyopathy, MODS, HELLP syndrome. Data were collected as per Performa (facility based Maternal Near Miss Review Form [MNM-R FORM] and statistical analysis was performed. Results: The cases of near miss have 2 or more factors responsible for it. In this study,23% of SAMM are due to lack of resources and Lack of transport from home to health care facility. 20% due to lack of human resources.11% due to lack of awareness. Other responsible for minor contributory factors. Conclusions: SAMM can be decreased by identifying factors responsible for it and steps taken to resolve them. Step by step improvement to be done as all the factors are modifiable.